Biochemical changes in ridge gourd (Luffa acutangula l.) cultivars induced by root knot nematodes (Bangladesh Journal of Botany, 2020)
Biochemical changes in different ridge gourd cultivars inoculated with Meloidogyne incognita were investigated. All the parameters showed higher activity during post infection period, both at shoots and roots level. Cultivar Priya had significant higher activity of phenylalanine ammonia lyase (PAL) than rest of the cultivars in infected shoots. However, it had only significant higher PAL expression in infected roots of Harsha cultivar of ridge gourd. All the cultivars showed non-significant changes in infected shoots for tyrosine ammonia lyase (TAL) contents. In infected roots, culture BSS 1009 showed significant increase in TAL than cultivars Harsha and Aarti, however Priya only had significant higher expression of TAL than culture Harsha. For peroxidase contains, all the cultivars displayed significant variation at infected shoots and roots level. Highest increase in peroxidase was noticed in resistant than susceptible cultivars in infected shoots of different ridge gourd cultivars. In general, with few exceptions resistant cultivars had higher catalase activity both in infected shoots and roots of different ridge gourd cultivars.